Impaired cooperation between IFT74/BBS22–IFT81 and IFT25–IFT27/BBS19 causes Bardet-Biedl syndrome. Issue 10 (9th December 2021) - Zhou, Zhuang; Qiu, Hantian; Castro-Araya, Roiner-Francisco; Takei, Ryota; Nakayama, Kazuhisa; Katoh, Yohei
Abstract: The IFT-B complex mediates ciliary anterograde protein trafficking and membrane protein export together with the BBSome. Bardet-Biedl syndrome (BBS) is caused by mutations in not only all BBSome subunits but also in some IFT-B subunits, including IFT74/BBS22 and IFT27/BBS19, which form heterodimers with IFT81 and IFT25, respectively. We found that the IFT25–IFT27 dimer binds the C-terminal region of the IFT74–IFT81 dimer and that the IFT25–IFT27-binding region encompasses the region deleted in the BBS variants of IFT74. In addition, we found that the missense BBS variants of IFT27 are impaired in IFT74–IFT81 binding and are unable to rescue the BBS-like phenotypes of IFT27 -knockout (KO) cells. Furthermore, the BBS variants of IFT74 rescued the ciliogenesis defect of IFT74 -KO cells, but the rescued cells demonstrated BBS-like abnormal phenotypes. Taken together, we conclude that the impaired interaction between IFT74–IFT81 and IFT25–IFT27 causes the BBS-associated ciliary defects.